Special education in contemporary society: An introduction to exceptionality - Gargulo, Richard M. (Canada : Sage Publications, Incorporation, 2015)
The text provides a rare glimpse into the lives of persons with exceptionalities, as well as their families and teachers. Focusing on a person-first orientation to human exceptionalities across the life span.
Part 1. Foundations of special education -- Part 2. A study of individuals with special need .
Includes bibliographical references and index.
Keywords: SPECIAL EDUCATION